Understanding and Evaluating Employee Volunteering Platforms for Colgate Palmolive Ltd. - Negi, Saloni (ATLAS SkillTech University, 2024)
This report is a comprehensive analysis of my internship where I have performed various activities like understanding social media presences of shortlisted employee volunteering platforms. The analysis aimed to assess the platforms' engagement strategies, audience interaction, and overall brand reputation on social media. Through this research, I gained insights into the platforms' outreach and impact, which proved valuable in understanding their effectiveness in connecting with Colgate-Palmolive employees. The findings highlighted the significance of visually appealing content and active audience engagement to foster a sense of community and advocacy. I recommended leveraging influencer collaborations, user-generated content, and targeted campaigns to further enhance the platforms' social media presence and drive meaningful employee engagement in volunteering activities. As an MBA student interning at Colgate-Palmolive India, I undertook an in-depth analysis of the social media presences of the shortlisted volunteering platforms. This analysis provided crucial insights into the platforms' communication strategies, audience engagement, and brand reputation in the digital landscape. The findings underscored the importance of diverse and visually compelling content, as well as the active interaction with the audience to create a sense of community and trust. Leveraging influencer partnerships and user-generated content emerged as effective strategies to amplify the platforms' impact and expand their reach. My recommendations emphasized the need for targeted social media campaigns and dedicated hashtags to maximize user engagement and promote a cohesive brand presence. Overall, the analysis and recommendations contributed to enhancing the platforms' social media outreach, aligning it with Colgate-Palmolive's CSR objectives, and fostering a culture of social responsibility and employee empowerment within the organization.
Project Report on Understanding and Evaluating Employee Volunteering Platforms for Colgate Palmolive Ltd. (2022-24) Under the Guidance of Prof. Zuleika Homavazir
Keywords: Social Media; Marketing